ASPEK BIO-EKOLOGI DAN PEMANFAATAN KERANG MARGA ANADARA (MOLLUSCA: BIVALVIA: ARCIDAE) - Eka Sulistiyaningsih; Ucu Yanu Arbi (OSEANA, 2020)
One of various shellfish in Indonesia waters that has high economic value is genus Anadara, especially as an edible marine species. Anadara is traditionally known in the trade as blood cockles. There are approximately 100 species of blood cockles in subfamily Anadarinae, the largest member of family Arcidae. Systematic of Anadarinae still does not provide certainty until now, including because there are many variations between species. Anadara, and Arcidae, in general, is one of the most abundant families of mollusc in tropical waters, and spread out in almost all of the coastal waters and found in the basis of subsystems. Its growth will be better on soft mud substrate than sandy mud substrate. Blood cockles are known as a filter feeder that feeds using gills on plankton, especially on phytoplankton. The demand for blood cockles is increasing, thus encouraging production efforts that do not only rely on harvesting from nature but through cultivation also that has been done in several places in Indonesia, such as in Sumatra and Java. This paper discussed taxonomy and classification, morphology and anatomy, habitat and distribution, reproduction and aquaculture, diet and feeding habit, and economic value of blood cockles.